Revealing the three-dimensional murine brain microstructure by contrast-enhanced computed tomography - Balcaen, Tim; Piens, Catherine; Mwema, Ariane; Chourrout, Matthieu; Vandebroek, Laurens; Des Rieux, Anne; Chauveau, Fabien; De Borggraeve, Wim M.; Hoffmann, Delia; Kerckhofs, Greet (Frontiers in Neuroscience, 2023)
To improve our understanding of the brain microstructure, high-resolution 3D imaging is used to complement classical 2D histological assessment techniques. X-ray computed tomography allows high-resolution 3D imaging, but requires methods for enhancing contrast of soft tissues. Applying contrast-enhancing staining agents (CESAs), which ameliorate the X-ray attenuating properties of soft tissue constituents, is currently the most accessible method for lab-based CT systems and is referred to as contrast-enhanced computed tomography (CECT). Despite the large number of chemical compounds that have successfully been applied as CESAs for imaging brain, they are often toxic for the researcher, destructive for the tissue and without proper characterization of affinity mechanisms. In this study, we evaluated two sets of chemically related CESAs (organic, iodinated: Hexabrix and CA4+ and inorganic polyoxometalates: 1:2 hafnium-substituted Wells-Dawson phosphotungstate and Preyssler anion), for CECT imaging of murine hemispheres. Differences in the penetration rate, effect on tissue integrity and affinity for tissue constituents have been observed for the evaluated CESAs. To show the added value of CECT to investigate myelination in animal models, we selected the CESA that provided the highest contrast between grey and white matter and we applied it successfully to a cuprizone-induced demyelination model.